Pengaruh Green Marketing Communication Terhadap Brand Image Fore Coffee (Jurnal Ilmu Komunikasi dan Bisnis, 2025)
Environmental issues caused by the increase in plastic waste have prompted coffee brands such as Fore Coffee to adopt green marketing communication strategies through the #FOREssentiallyYou and #FOREsponsible campaigns. This study aims to analyze the effect of green marketing communication strategies on the Fore Coffee brand image. The method used is explanatory quantitative research. Data were collected through an online questionnaire distributed to 100 Fore Coffee consumers aged 18-40 years who had purchased or consumed Fore Coffee, were concerned about environmental issues, and had seen environmental messages or campaigns from Fore Coffee. Data analysis was performed using normality tests, linearity tests, heteroscedasticity tests, t-tests, simple linear regression, and determination coefficients. The results showed that green marketing communication had a significant effect on brand image. The environmental message clarity indicator was the most dominant factor in shaping positive consumer perceptions, while audience engagement had the lowest but still positive influence. This study emphasizes the importance of message clarity and consistency in corporate actions in enhancing a brand image committed to sustainability.